PENDIDIKAN NILAI DAN SPIRITUAL (PNS) DALAM LAYANAN BIMBINGAN DAN KONSELING DI SMP NEGERI 1 BANTUL YOGYAKARTA - Yanto, Yanto (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2019)
The implementation of value and spiritual education in guidance and counseling services is the aboligation of schools. It has implications for the nature of individual guidance and counseling to help individuals for develop human nature by empowering faith, reason, dan willingness who has given by God so that individuals can develop properly and firmly as God guides. The research method used is qualitative with a descriptive approach and data collected by interview, observation and documentation. Findings data were analyzed using conten analysis techneques. The informan are theachers, students, and parent of students.The result of this study founded, 1) education of values and spirituality in SMP Negeri 1 Bantul is not only become the responsibility of the guidance dan counseling teacher, it is was includes within thes school curriculum structure that described in each subject as a hidden curriculum. 2) The values and spiritual education of students is very dependent on education in their family. 3) There isa good tolerance between Muslim dan non-Muslim students during implementation of classroom learning. 4) School appreciation and support in organizing religious activities for Muslim dan non-Muslim students. 5) The school cooperates with other parties (in collaboration with one of the churches) to provide religious education for non-Muslim students.